Now you see her : a novel - Patterson, James, 1947-; Ledwidge, Michael (New York : Little, Brown and Co., 2011)
A successful lawyer and loving mother, Nina Bloom would do anything to protect the life she's built in New York-- including lying to everyone, even her daughter, about her past. But when an innocent man is framed for murder, she knows that she can't let him pay for the real killer's crimes.
Keywords: Women lawyers -- New York (State) -- New York -- Fiction; Key West (Fla.) -- Fiction; Suspense fiction